Study on transport characteristics of nanofluid as a cooling medium for vehicle engine - Kang, Hang (2021)
The internal combustion engine has become one of the indispensable thermal power machineries in modern society, whilst the performance and lifespan of combustion engine are seriously affected by its operating temperature. However, without a cooling system it is impossible to maintain engine in various working conditions always operating within the optimal temperature range. Among the existing methods of enhancing the cooling system, replacing the traditional cooling medium with nanofluid is a promising and efficient strategy. This thesis investigates the key technology of cooling system based on nanofluid for combustion engine in vehicles. From the theoretical and numerical perspective, the major challenge for nanofluid simulation is to effectively capture the coupling two-phase flow, mass and heat transfer in nanofluid flow. To achieve this goal, this thesis formulates three sets of governing equations to describe these multiphase transport phenomena of nanofluid. In so doing, the theoretical models can effectively describe liquid-particle two-phase flows under the impacts of drift velocity resulted from Brownian and thermophoretic diffusion. Importantly, a couple of multi-distribution-function lattice Boltzmann (LB) algorithms are developed to solve these equations, by which detailed numerical studies of not only nanofluid flow and mass transfer under isothermal condition but also transport characteristics under non-isothermal condition were obtained. The simulation results given by the LB model clearly reveal distinct flow, mass and heat transfer characteristics of nanofluid; the proposed LB models are demonstrated as viable and effective numerical tools for studying these complex transport phenomena in nanofluid. On the other hand, in order to develop a new type of nanofluid which is suitable for vehicle engine water jacket, the Al2O3 nanoparticles with ethylene glycol (EG) and water mixture are used to prepare nanofluid. At the same time, the basic physical properties (viscosity and thermal conductivity) of proposed nanofluid are measured. Then, a test rig with square tube is built to investigate the forced convective and subcooled flow boiling of nanofluid under similar working conditions in engine. The experiments were performed at different levels of operating variables such as degree of superheat temperature (10-25℃), volume flow rate (400-1000L/h) and nanoparticle volume fraction (0.2-1.0%). It can be concluded that the increase of flow rate can significantly improve the heat transfer efficiency at low degrees of superheat. Excessive degrees of superheat will inhibit the increase in heat transfer by the flow rate. The maximum increase in convective heat transfer coefficient is 67.2% for the Al2O3 EG-water nanofluid with particle volume fraction of 0.6% compared to EG-water base fluid for the same volume flow rate. These experimental results also demonstrate that nanofluid can effectively improve the convective heat transfer coefficient of traditional base fluid with optimized particle volume fraction.